A Study on Hybrid WECSM Setup During Cutting of E-Glass Fibre Epoxy Composite - Malik, Anup; Samir, Sushant; Manna, Alakesh (Asian Journal of Engineering and Applied Technology, 2013)
Some of the well known non-conventional machining processes like electrical discharge machining (EDM), wire electrical discharge machining (WEDM) etc. are not suitable for machining of electrically nonconductive ceramic materials. E-glass fibre epoxy composite is a nonconductive ceramic material hence it is difficult to machine by the above mentioned machining processes. However, this material can be machined with conventional machining but compromise with accuracy, surface texture and micro cutting. Keeping in view, a hybrid machining setup is designed and fabricated based on the combined of both electro chemical machining (ECM) and WEDM technique. The fabricated wire electrochemical spark machining (WECSM) setup is utilized to machine e-glass fibre epoxy composite. This paper presents the results during machining of e-glass fibre epoxy composite on fabricated WECSM setup. The effect of different parameters of developed WECSM setup on machining performance characteristics such as material removal and spark gap width have been explain through various graphs. Test results and thereafter analysis show that the DC supply voltage and electrolyte concentration are most significant parameters on material removal and spark gap width. This practical research analysis on developed WECSM setup will provide new guidelines to the modern researchers and manufacturing engineers.